2023
DOI: 10.1007/s12079-023-00722-5
|View full text |Cite
|
Sign up to set email alerts
|

Why do humans need thrombospondin-1?

Abstract: Matricellular proteins comprise several families of secreted proteins that function in higher animals at the interface between cells and their surrounding extracellular matrix. Targeted gene disruptions that result in loss of viability in mice have revealed critical roles for several matricellular proteins in murine embryonic development, including two members of the cellular communication network (CCN) gene family. In contrast, mice lacking single or multiple members of the thrombospondin (THBS) gene family r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 82 publications
2
4
0
Order By: Relevance
“…Efferocytosis of neutrophils by macrophages was also greatly enhanced following macrophage treatment with TSP-1 (Fig. 3e), in line with a previous study suggesting that TSP-1 acts as a bridge between neutrophils and macrophages to facilitate efferocytosis 41 . Finally, TSP-1 enhanced expression of CD206 and arginase-1 in the presence of anti-inflammatory cytokines (IL-4/ IL-13 or IL-10), demonstrating that TSP-1 accelerates macrophage polarization towards an anti-inflammatory and pro-repair phenotype (Fig.…”
Section: Articlesupporting
confidence: 91%
See 2 more Smart Citations
“…Efferocytosis of neutrophils by macrophages was also greatly enhanced following macrophage treatment with TSP-1 (Fig. 3e), in line with a previous study suggesting that TSP-1 acts as a bridge between neutrophils and macrophages to facilitate efferocytosis 41 . Finally, TSP-1 enhanced expression of CD206 and arginase-1 in the presence of anti-inflammatory cytokines (IL-4/ IL-13 or IL-10), demonstrating that TSP-1 accelerates macrophage polarization towards an anti-inflammatory and pro-repair phenotype (Fig.…”
Section: Articlesupporting
confidence: 91%
“…we tested whether TSP-1 affects neutrophil and macrophage migration and death, as well as efferocytosis and macrophage polarization. Although some reports have suggested that TSP-1 promotes neutrophil and macrophage migration 41 , we clearly observed an inhibition of migration when cells were treated with TSP-1, similarly to our observations with CGRP (Fig. 3c).…”
Section: Articlesupporting
confidence: 90%
See 1 more Smart Citation
“…15 Considering previous reports on the interaction of THBS1 with the immune system, the multifunctionality of this protein and miRNAs deregulation, we hypothesized that its concentrations might influence the incidence of severe infections during AHSCT, making THBS1 a potential biomarker of complications during ASCT. 16 This study aimed to assess the clinical value of a blood serum THBS-1 concentration that could serve as a predictive biomarker for infectious-related adverse events during AHSCT.…”
Section: Introductionmentioning
confidence: 99%
“…The top 10 proteins which were significantly up-regulated in HEPM-EXO showed a high intercorrelation and were reported to be associated with cell growth, cell communication and signal transduction. [25][26][27][28][29][30][31][32][33][34] HEPM-EXO may rely on some of these proteins to regulate the proliferation and migration of HIOEC. Among these proteins, THBS1 was frequently associated with exosomal regulation of cell migration.…”
mentioning
confidence: 99%